A novel end-to-end test for combined dosimetric and geometric treatment verification using a 3D-printed phantom - Mertens, Lena; Fleckenstein, Jens; Steil, Volker; Schneider, Frank (Medical dosimetry, 2022)
The dosimetric and geometric accuracy are important components to ensure safe patient treatment in radiation therapy. Therefore, these components must be checked during quality control. This work presents a possible solution for the determination of the geometric isocenter deviation in the entire treatment chain. Additionally, the dose measurement of the established end-to-end test workflow measured in the same procedure as the geometric deviation is described. An in-house designed end-to-end test phantom went through the entire procedure of a standard patient treatment and the dosimetric and geometric accuracy were determined. At 3 linear accelerators (linac), the phantom was positioned either with cone beam computed tomography or with surface guidance. In this position, a Winston-Lutz test was performed and the deviations of the gantry, collimator and couch isocenter measurements to the phantom position were determined. Additionally, a dose measurement in the phantom was performed and compared to the dose predicted in the treatment planning system. To validate the results obtained with the in-house designed phantom, comparative measurements with commercial phantoms were performed. According to the performed end-to-end test, 2 out of the 3 linacs showed isocenter variations larger than 1 mm for collimator and gantry rotations and larger than 2 mm for couch rotations. With an isocenter variation of less than 1 mm for collimator and gantry rotations, 1 linac fulfilled the tolerance for stereotactic treatments without couch rotation. With couch rotation, an isocenter variation of less than 2 mm was detected at this linac, which fulfilled the tolerance for IMRT treatments. The mean dose deviation between measurement and treatment planning system was 1.82% ± 1.03%. The results acquired with the UMM phantom did not show statistically significant deviations to those acquired with relevant other commercial phantoms. The novel end-to-end test procedure allows for a combined dosimetric and geometric treatment evaluation. Besides the commonly performed dose end-to-end test the geometric isocenter deviation within a patient treatment workflow was evaluated and categorized for IMRT or SBRT.
Online verfügbar: 7 March 2022, Artikelversion: 30 April 2022
Gesehen am 16.10.2023